Personal Branding Akun (@arisdogonzalez) Sebagai Aktivis LGBTQ+ di Indonesia Melalui Media Sosial Instagram - Palandi, Joan Alexandra Jethrovany; Joni, I Dewa Ayu Sugiarica; Pradipta, Ade Devia (E-Jurnal Medium, 2024)
The rapidly changing technological landscape, Indonesian society is deeply integrated with the internet and social media. Social media platforms such as Instagram are particularly popular, and personal branding is a growing priority for users. As social media platforms such as Instagram continue to gain in popularity, personal branding has become an increasingly important endeavor for individuals seeking to distinguish themselves and establish their identity online. LGBTQ+ activist Arisdo Gonzalez, for example, has built a powerful image online and uses Instagram to showcase who he is in both his professional and personal life. This qualitative study examines how Arisdo Gonzalez has shaped his personal branding on Instagram using eight key concepts identified by Peter Montoya. By analyzing interviews with Arisdo Gonzalez, book and journal texts, and observations of his social media accounts, this research shows that he has effectively utilized these concepts to enhance his personal branding.